Governance practices and corporate performance: Assessing the competence of principal-based guidelines - Marwan Mansour; Hafiza Aishah Hashim; Zalailah Salleh; Waleed M. Al-ahdal; Faozi A. Almaqtari; Murad Abdulsalam Qamhan (Cogent Business & Management, 2022)
This study aims to investigate the relationship between corporate governance (CG) compliance and corporate performance in Jordan. We develop a corporate governance index (CGI) and investigate its impact on firms' performance. The index consists of 32 unique internal governance attributes that were built based on Jordanian governance Code. This study used a quantitative research method using panel dataset analysis of 672-firm year observations. Fixed effects regression model was employed to analyse the governance-performance nexus. To infer correctly, we re-examine the main analysis using a well-developed dynamic generalized method of moments (GMM) estimator to overcome possible endogeneity concerns. Consistent with prior studies in developed and developing countries in the governance literature, our findings robustly disclose that compliance with CG guidelines is a determinant of corporate performance of listed firms in Amman Stock Exchange (ASE) during period 2009-2016. The results indicate that a better degree of compliance with the Jordanian code and guidelines is positively and significantly related with better performance of publicly listed firms. This study contributes theoretically and practically to growing but under-developed literature on governance compliance and corporate performance in developing countries. Therefore, this research has useful implications for developing countries, stock market authorities, policymakers, firms' directors, and academicians.
Keywords: 650; corporate governance index; firms' performance; Jordan; Market share